Analisis Pencapaian Tujuan Hukum terhadap Penerapan E-Court di Pengadilan Agama Belopa: Analysis of the Achievement of Legal Goals on the Implementation of E-Court in the Belopa Religious Courts - Mohammad Farisan Auzan; Muammar Arafat Yusmad; Firman Muhammad Arif; Wildana Arsyad (BUSTANUL FUQAHA: Jurnal Bidang Hukum Islam, 2025)
This study aims to analyze the implementation, stakeholder perceptions, problems and solutions, as well as the urgency and achievement of legal objectives regarding the use of the e-court application at the Religious Court of Belopa. The research employs interview, observation, and documentation methods with a descriptive qualitative approach. The findings show that the e-court system has been implemented from the administrative stage to the trial process at the Religious Court of Belopa. However, there are still several issues in its implementation. First, the use of the application remains limited, particularly among non-advocate users, compared to legal professionals in case resolution. The main obstacles identified include the electronic payment (e-payment) method, frequent server maintenance of the e-court system, and the public’s limited knowledge. As a result, only active individuals and legal representatives are among the few who regularly utilize the e-court application in legal proceedings. Improving the effectiveness of the e-court system is an ongoing effort to provide the best service to the people of Luwu Regency in accessing justice. The study recommends the establishment of a Memorandum of Understanding (MoU) or cooperation agreement between the Religious Court of Belopa and local banks, upgrading the e-court server by the Supreme Court to a higher capacity to minimize maintenance interruptions, and organizing both direct and indirect training and socialization programs for the Luwu Regency community through collaboration between the Religious Court of Belopa and village government officials.